Libya : desert land in conflict - Gottfried, Ted. (Brookfield, Conn. : Millbrook Press, 1994)
Text and photographs discuss the geography, history, religion, and economy of this North African country, with an emphasis on its controversial dictator Muammar Qaddafi and its role in current affairs.
Includes bibliographical references (p. 148-149) and index.
Book Links (A.L.A.).
School Library Journal.
Wilson's Junior High School.
7-9
Young Adult
Keywords: Libya; Libya -- Juvenile literature; Libya -- Politics and government -- 1969- -- Juvenile literature; Libya; Libya -- Politics and government -- 1969-; Libya -- Politics and government